Crafting the future of bone regeneration: the promise of supramolecular peptide nanofiber hydrogels - Wan, Longbiao; Yao, Xiaoyue; Pan, Jiali; Xiang, Ziyang; Fu, Dongjie; Ye, Qingsong; Wu, Fei (Frontiers in Bioengineering and Biotechnology, 2025)
Bone tissue engineering has rapidly emerged as an ideal strategy to replace autologous bone grafts, establishing a comprehensive system centered on biomaterial scaffolds, seeding cells, bioactive factors, and biophysical stimulation, thus paving the way for new horizons in surgical bone regeneration. However, the scarcity of suitable materials poses a significant challenge in replicating the intricate multi-layered structure of natural bone tissue. Supramolecular peptide nanofiber hydrogels (SPNHs) have shown tremendous potential as novel biomaterials due to their excellent biocompatibility, biodegradability, tunable mechanical properties, and multifunctionality. Various supramolecular peptides can assemble into nanofiber hydrogels, while bioactive sequences and factors can be embedded through physical adsorption or covalent binding, endowing the hydrogels with diverse biochemical properties. Finally, this review explored the future challenges and prospects of SPNHs in bone tissue engineering, with the aim of providing insights for further advancements in this field.